Prostitutes and Prophylaxis: Venereal Disease, Surveillance, and Discipline in the Canadian Army in Europe, 1939-1945 - Pratt, William (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2015)
The wastage of Canadian manpower due to venereal disease (VD) during World War II was an ongoing problem for the Canadian Army. Military authorities took both medical and disciplinary measures in attempt to reduce the number of soldiers that were kept from regular duties while under treatment. The study of the techniques employed to control sexual behaviour and infection places the Canadian Army in a new historical perspective as a modern institution which sought to establish medical surveillance and disciplinary control over soldiers’ bodies. This study also explores Canadian soldiers’ sexual behaviour overseas, showing their engagement in a broken system of regulated prostitution, and with European women who were coping with war’s destabilization and strain by participating in the sex trade. Agents of the Canadian Army overseas extended their disciplinary and surveillance functions from soldiers to their sexual partners. VD rates were low when formations were in combat, but rose to alarming rates when they were out of the line, suggesting that individual agency and sexual choice trumped the efforts of modern discipline.